French social theory - Gane, Mike (Theory, culture & society (Unnumbered), 2003)
French Social Theory, an extraordinarily accomplished book provides a peerless account of the French tradition. French Social Theory provides a systematic account of French social theory from the aftermath of the French Revolution (St Simon, Bazard and Comte) to the contemporary scene dominated by Kristeva, Deleuze, Bourdieu and Baudrillard; divides French social theory into three logically coherent cycles: 1800-80 (Positivist); 1880-1940 (Anthropological); 1940-2000 (Marxist); French Social Theory provides a detailed guide to the three phases of postwar French social theory - existential, structural and post-structural; and situates the discussions of individuals and schools in the relevant social and political contexts. French Social Theory is a masterpiece of erudition and scholarship but is written throughout in an engaging and informative style.